LEVEL OF SECURITY AND PERCEPTION OF SECURITY IN HOUSING PATTERN PERMEABILITY (CASE STUDY : PERMANA INDAH, TAMAN BUMI PRIMA, AND PONDOK MUTIARA HOUSING) - Indrasari (NIM. 25205006), Fenita
This research was intended to compare level of security and residents perception of security in three different housing permeability pattern with similar characters. North Cimahi was chosen as study area because has a potential to develop into an urban area with all complex problems entitled, especially crime. This part of the city has placed housing for middle income group and a tendency to become a gated community representative area. Data was collected through observation and structured interview with society figures in related housing and questionnaires spread to housing residents purposively based on house and neighborhood level of permeability. Quantitative and qualitative analysis method was used to get findings. To make a better explanation of quantitative results from simple statistics, pattern-matching method was done. Analysis results have proven that level of security is related with housing permeability pattern with effects in time, level of security is relatively higher at day and the contrary at night. Level of security, especially crime experience, would effect perception of security. This perception then would effect respond, in form of security control and surveillance. However behavior respond is not closely connected to perception, but to sense of community instead. Neighborhood permeability level (TPL) is related to perception of security towards house location and crime high-risk area. Two opposite patterns are: in high permeability level housing, the lower TPL would be considered less secure and would have lower level of security. While in low permeability level housing, the lower TPL would be considered more secure and would have higher level of security. There are elements that defining both level of security and perception of security, which are amount of vehicle access and length of block. The more amount of vehicle access and the more length of a block would have resulted a relatively lower level of security and perception of security. Based on findings, suggested length of a block is less than 200 meters and adapted to calculation of layout and circulation efectivity in the housing area. Based on findings a conclusion about secure housing design to middle income group was made. Secure housing design would tend to have a low permeability level because adjusted to housing nature as a semi-public area, it gives higher privacy and comfort for the residents. However still need to be considered of good blending between the edge of housing area and its surrounding. Pedestrian access need to be unrestricted as possible but surveillance to the access still would be needed. Meanwhile vehicle access has to be restricted. Purpose of this housing edge arrangement is to avoid housing area of being socially isolated.